Conference on Medical Education and Research Writings during Arbaeen at College of Medicine, University Warith Al-Anbiyaa, and University of Karbala 22–23 and 26 July 2026 - Mulazim Hussain Bukhari; Ali Abed Saadoon; Ali Abutiheen (Journal of the Pakistan Medical Association, 2026)
An academic programme spanning three days took place in Karbala, Iraq on 22–23 and 26 July 2026, linking medical education and training in scientific writing to the service orientation of the Arbaeen pilgrimage. Workshops held at the College of Medicine, University of Warith Al-Anbiyaa and at the College of Medicine, University of Kerbala brought together Iraqi and Pakistani educators and clinicians to discuss responsible artificial intelligence, qualitative research, scientific writing, curriculum integration, regenerative medicine, precision geriatric care, radiology, surgery, and disaster management. Practical workshops enabled participants to move away from information transfer to application. A critical synthesis revealed four interlinked themes: service and scholarship as an integrated continuum; learning by doing; responsible innovation; and academic solidarity across borders. The programme provided a forum for future mentorship and collaboration in research but future events will need to include prospective evaluation and follow-up of the results of the academic activities. These areas can shape the planning and evaluation of future conferences.